ANALISIS PERBANDINGAN PENILAIAN KINERJA BPR DENGAN PENDEKATAN BALANCED SCORECARD - Putri, I Gusti Agung Pramesti Dwi; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 12 No 1 (2015), 2015)
Balanced scorecard is a contemporary performance assessment tool created by Robert  S. Kaplan and David P. Norton. Balanced scorecard assess the performance of the company by financial and non financial perspective. The purpose of this study is to compare the performance of BPR Mertha Sedana and BPR Bali Harta Santosa using the balanced scorecard to determine the differences. Financial performance is measured by financial ratios. Customer performance is measured by customer statisfaction. Internal business process performance is measured by the growth of innovation. Growth and learning  performance is measured by employee statisfaction and motivation, employee productivity, and employee retention. Alternative hypothesis testing research is Independent sample t-tes and Mann-Whitney U. The results of this study show that there are differences  in financial performance, customer performance, and growth and learning performance between BPR Mertha Sedana and BPR Bali Harta Santosa.  The difference in internal business process could not be known because the deviation standard for both BPR is nil.
Keywords: balanced scorecard, performance measurement, BPR